A governança reprodutiva na América Latina: um olhar através da lente da Justiça Reprodutiva - Silva, Ingrid Schimith Miranda da (2023)
The objective of this article is to analyze Reproductive Governance (RG) in Latin America and, through the lens of Reproductive Justice (RJ), highlight that the institutionalized colonial heritage in the countries of the region affects multiply marginalized bodies differently, thus directly influencing their reproductive experiences. While reproductive experiences are globally interconnected, mortality and violence directed at the female body is unevenly divided according to location, race and class. Therefore, the demographic, social and historical dynamics of the place where an individual lives, have the ability to dictate their rights, their quality of life and their death perspective. In this sense, this article proposes a discussion that has been little developed in the works of RG through the lens of RJ so far, by looking at the phenomenon with a critical view of history and the different powers that keep groups of individuals on the margins of society and intentionally use this form of violent governance to treat certain reproductive bodies as disposable and undesirable. Therefore, it will be divided into 4 sections: first, the introduction of the centrality and capillarity of reproduction in all aspects of life. Second, the definition of Reproductive Governance and Reproductive Justice concepts. Third, the description of Latin American landscape regarding its reproductive rights. Finally, final considerations will be made